Integrating Scientific Attitude to Realize Pancasila Learner Profile in Science Learning - Ummah, Wihda Tul; Yohamintin, Yohamintin (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Investigate the integration of scientific attitudes in Natural Science learning and its impact on the character development of Pancasila Students. With the increasing need to form a generation that is not only academically intelligent but also has a strong character, this study focuses on how scientific attitudes can be integrated into the science curriculum to support Pancasila values. Methodology: This study used a literature review approach by analyzing 40 relevant articles and studies published between 2014 and 2024. Data were collected through searches in academic databases, and qualitative analysis was conducted to identify key themes related to integrating scientific attitudes and character. Main Findings: This study found that integrating scientific attitudes in Natural Science learning is very important to shape students' characters under Pancasila values. Effective learning models, such as project-based learning and group discussions, can increase student engagement and understanding of science concepts and encourage positive behaviors such as tolerance and cooperation. These findings align with previous studies showing active and collaborative learning approaches can increase student engagement. Novelty/Originality of this study: The holistic approach that combines scientific attitudes and the character of Pancasila Students in Indonesia's education context. The results of this study provide important implications for educators and policymakers to adopt a learning model that integrates scientific attitudes and character education in the curriculum. Thus, this study contributes to the development of better educational practices relevant to the needs of the times and prepares students to become responsible and ethical individuals in society.